2016
DOI: 10.3855/jidc.8124
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in patients with urinary tract infections and the impact on empiric therapy in Serbia

Abstract: Introduction: Surveillance of antimicrobial resistance is essential in establishing treatment guidelines for urinary tract infections. The aim of this pilot study was to analyse resistance rates of pathogens, across different demographics and determine whether adjustments in empiric therapy should be considered for different age and gender groups. Methodology: A 5-year retrospective study included 256 patients hospitalised, under the initial diagnosis of Fever of Unknown Origin who were then subsequently diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
2
4
0
2
Order By: Relevance
“…Despite the fact that the statistics were not significant between marital status and gender with UTI, yet high percentages of married respondents (n = 70/101, 69.3%) and females (n = 57/91, 62.6%) were in UTI positive group. These were also reported in other studies [14,15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the fact that the statistics were not significant between marital status and gender with UTI, yet high percentages of married respondents (n = 70/101, 69.3%) and females (n = 57/91, 62.6%) were in UTI positive group. These were also reported in other studies [14,15].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the respondents of the study were females 91 (71.1%) in comparison to males, which were 37 (28.9%). Showing considerable differences in the prevalence of UTI among outpatient visiting hospital setting, this agrees with a study from Nigeria, which showed that the prevalence of UTI was very high in females attending hospitals for UTI cases 111 (74%) compared to males 39 (26%) [14,15] as well as study conducted in Iran reported high proportion of UTI among outpatients were females (85.2%) [4]. These results indicated that females were prone to UTI as these were attributed to the nature of urogenital tract of the females; it is proximity to the anus and also lacking the bacteriostatic nature of prostatic secretions of male [14,15,20].…”
Section: Discussionsupporting
confidence: 89%
“…Data analysis considered the timing of infection and LOS for the duration of the infection, adjusted for patient comorbidity upon admission to avoid possible overestimation of the effect of resistance, [57][58][59] and controlled for various potential confounding demographic and clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Gerek toplum kaynaklı gerekse hastane kaynaklı ÜSİ'de ilk sırada yer alan etken Escherichia coli'dir (2,3). İdrar kültüründe üreyen patojenin tanımlanması ve antibiyotik duyarlılık testlerinin sonuçlanması için belli bir süreye ihtiyaç duyulması nedeniyle, ÜSİ'de sıklıkla ampirik antibiyotik tedavisi başlanmaktadır (4,5). Uygun olmayan ampirik tedavi, antibiyotiklerin değiştirilmesine neden olmakta; bu da zaman kaybına, hastanede yatış sürelerinin uzamasına, antibiyotik direncinin gelişmesine ve maliyet artışına yol açmaktadır (4)(5)(6).…”
Section: Introductionunclassified
“…İdrar kültüründe üreyen patojenin tanımlanması ve antibiyotik duyarlılık testlerinin sonuçlanması için belli bir süreye ihtiyaç duyulması nedeniyle, ÜSİ'de sıklıkla ampirik antibiyotik tedavisi başlanmaktadır (4,5). Uygun olmayan ampirik tedavi, antibiyotiklerin değiştirilmesine neden olmakta; bu da zaman kaybına, hastanede yatış sürelerinin uzamasına, antibiyotik direncinin gelişmesine ve maliyet artışına yol açmaktadır (4)(5)(6). ÜSİ'de en sık saptanan etkenin ülkemizdeki antibiyotik duyarlılık profiliyle ilgili bilgiler, ampirik tedavide kullanılacak antibiyotiklerin seçiminde yol gösterici olmaktadır (1,2,4).…”
Section: Introductionunclassified